ANALYSIS OF POLICY PRIORITIES TO IMPROVE THE PERFORMANCE OF PUBLIC SERVICE APPARATUS IN URBAN VILLAGE OFFICES IN SEMARANG DISTRICT - Sri Rahayu; Yanu Setiyanto (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
The district office is one of the forefront public service agencies which its performance is directly felt and catched by the public, but the performance of its employees are stil not optimal. The main purpose of this research is to determine the priority of the employee's performance improvement policies of the district offices in the Semarang regional government. This research is using qualitative approach by analyzing the work ability, work facility, standard operational procedure and work discipline as the alternative variables in order to achieve the work performance improvement as the goals variable. The population of this research is 27 district offices in the Semarang renal government with the samples that being used are 13 persons hat consist the key informants, the main informants and the supporting informant who's being chosen though some determined criteria. The results of the analysis using AHP method find that the work discipline is the first priority, the work ability is the second, the standard operational procedure is the third priority and the work facility is the fourth priority with the consistency ratio (CR) value is 0,01. The study's conclusion is that work discipline improvement is the first priority in the way to the employee's performance improvement of the district offices in the Semarang regional government which shows that work discipline of the public service office's employees is still not in the way they were desired to be.